(untitled) (Eurasian Journal of Philology Science and Education, 2026)
This article offers a philological and cultural-philosophical analysis of the intellectual legacy of Murat Mukhtarovich Auezov, in which the central concept is the idea of “language as destiny.” Auezov regards language as the key factor in shaping Turkic identity, determining the nation’s spiritual trajectory and cultural survival. Of particular importance is his notion of “linguistic other-being,” describing the condition of a bilingual writer torn between the native and the “foreign” linguistic space. This phenomenon is examined in the article within the frameworks of translingualism and postcolonial criticism, highlighting its universal significance for post-Soviet cultural contexts. A philological reading of Hippocrene: Journeys to the Wells of Time and The Thread Linking Times reveals Auezov’s idiostyle: conceptual metaphors such as “path,” “thread,” and “spring” provide the philosophical framework of his texts; the blending of publicity and artistic discourse produces expressive resonance; and bilingual elements create a “double code” within the works. Special attention is given to the triad til – din – dil (“language – faith – spirit”), which functions as a matrix of Turkic identity. In addition, the author examines the interrelationship between linguistic and cultural categories in the works of Murat Auezov within the context of contemporary humanities. The article demonstrates that Auezov’s reflections extend beyond cultural commentary to acquire a profound philological dimension: language is interpreted as a source of poetics, a repository of national memory, and a medium of world-conceptualization. The novelty lies in a comprehensive interpretation of Auezov’s texts from the perspectives of modern philology, translingual studies, and postcolonial theory. The practical value of this work lies in its potential application to courses on the theory of language, the history of literature, and intercultural communication. Keywords: Murat Auezov; language as destiny; linguistic other-being; translingualism; philological analysis; Turkic identity; til – din – dil.